Processing Metrical Information in Silent Reading: An ERP Study - Kriukova, Olga; Mani, Nivedita (Frontiers in Psychology, 2016)
Listeners are sensitive to the metric structure of words, i.e. an alternating pattern of stressed and unstressed syllables, in auditory speech processing. Event-related potentials recorded as participants listen to a sequence of words with a consistent metrical pattern, e.g., a series of trochaic words, suggest that participants register words metrically incongruent with the preceding sequence. Here we examine whether the processing of individual words in silent reading is similarly impacted by rhythmic properties of the surrounding context. We recorded participants’ EEG as they read lists of either three trochaic or iambic disyllabic words followed by a target word that was either congruent or incongruent with the preceding metric pattern. ERPs to targets were modulated by an interaction between metrical structure (iambic vs. trochaic) and congruence: for iambs, more positive ERPs were observed in the incongruent than congruent condition 250-400ms and 400-600ms post-stimulus, whereas no reliable impact of congruence was found for trochees. We suggest that when iambs are in an incongruent context, i.e. preceded by trochees, the context contains the metrical structure that is more typical in participants’ native language which facilitates processing relative to when they are presented in a congruent context, containing the less typical, i.e. iambic, metrical structure. The results provide evidence that comprehenders are sensitive to the prosodic properties of the context even in silent reading, such that this sensitivity impacts lexico-semantic processing of individual words.